(untitled) (Global Journal of Science Frontier Research, 2022)
The presence of nature was evident in the cities and villages of Yemen - a country located on the southern tip of the Arabian Peninsula - with a varied topography between mountains plains deserts and islands Formerly Yemen was given many names For example the Greeks and Romans called it Arabia Felix while Arab historians called it green Yemen due to its fertility greenness and picturesque nature Ancient Yemeni settled in good geographical areas with suitable natural conditions and practised agriculture Despite the rugged terrain of the mountainous heights he built agricultural terraces on the mountains and found irrigation systems so he dug wells and built dams such as the Ma arib dam As a result settlements appeared that were not separated from nature but united or merged with it The local architecture appeared integrated with the land harmonious with the green spaces that permeate and surround it which form a distinctive image in all its cities and towns described by its visitors as a total garden Sana a old city is a vivid and extraordinary example of a traditional human settlement A city at the foot of Nuqum mountain founded by Shem son of Noah and inhabited for more than 2500 years This paper deals with the state of the green spaces in Sana a old city from past to present The importance of these spaces in the city s fabric its types characteristics roles and sustainability concepts that can be deduced Sana a old city is a model of ancient cities which contained urban green spaces surrounded by a group of towers that constitute a basic urban unit to form the city Thus green spaces spread in most parts surrounded by the dwellings walls creating a distinctive urban fabric The study aims to identify the current condition and determine the changes that have taken place to the green spaces in Sana a old city On-site spatial observation and interviews were conducted in addition to the available information on green spaces during the past decades The study revealed the extent of the deterioration of green spaces and the loss of many essential roles Results presented in this paper are necessary to consider these spaces dire state and give decision-makers recommendations to improve them and benefit from sustainable agricultural thought